Prospective Memory Training for Healthy Older Adults: A Systematic Review. Issue 3 (27th May 2022) - Tsang, Alex Pak Lik; Au, Alma; Lo, Herman Hay Ming
ABSTRACT: Objectives: This review systematically synthesizes existing evidence of prospective memory training for healthy older adults (> 55 years). Existing prospective memory training include strategy-based, process-based and combined regimens. Strategy-based training focuses on different mnemonics to compensate for aging declines in prospective memory. Process-based training aims to restore related cognitive processes to support prospective memory. Combined training utilizes both strategy-based and process-based regimens to enhance prospective memory performance. Methods: A total of 349 studies were identified from the Cochrane Library, EBSCO, PsycINFO and PubMed databases. Results: Using predefined inclusion and exclusion criteria, 11 studies were included in the review. There were six studies of strategy-based training, two studies of process-based training and three studies of combined training. Conclusions: Overall, strategy-based training appears to facilitate prospective memory for healthy older adults. However, it is impossible to draw conclusions for process-based and combined training due to the preliminary nature of current evidence. Clinical Implications: Mental imagery or the use of external aids can be useful strategy-based approaches to facilitate prospective memory in older adults. Strategy-based training should target multiple prospective memory phases simultaneously to encourage transfers. Further studies will be required to draw conclusions on the effectiveness of process-based and combined training.